Homeopathic Approach to Atherosclerosis: A Comprehensive Review - Dr.Nitin Singh (Revista Electronica de Veterinaria)
-Atherosclerosis is a chronic inflammatory disease and a leading cause of death worldwide. Conventional treatments manage symptoms but often fail to address underlying causes. Homeopathy offers a holistic approach, targeting the root causes of the disease. This review explores the homeopathic understanding of atherosclerosis, its pathogenesis, risk factors, clinical manifestations, and diagnosis. Homeopathic remedies, such as Allium cepa, Arnica montana, and Ginkgo biloba, have been traditionally used to treat atherosclerosis. A comprehensive homeopathic treatment approach involves evaluating the patient’s physical, emotional, and mental health to select a remedy that matches their unique symptom profile. While more research is needed, homeopathy may be a useful adjunct to conventional treatment for atherosclerosis. Introduction-Atherosclerosis is a chronic inflammatory disease characterized by the accumulation of lipids, macrophages, smooth muscle cells, and fibrous elements in the large arteries, leading to plaque formation, vascular narrowing, and eventual organ ischemia.(6) cardiovascular disease is the leading cause of death worldwide. Conventional treatment options are available while effective in managing symptoms, often fail to address the underlying causes of the disease. Homeopathy, a holistic system of medicine, offers a promising approach to treating atherosclerosis by targeting the root causes of the disease